Upplevelseproduktion i projektledning : Hur projektledare kan använda sig av modeller för upplevelseproduktion - Grönlund, Martin; Wemstad, Sara (2011)
Through experiences from work and internships we have become aware of the importance of a well functioning project management in experience productions. Thus we have chosen to study how the project participants of Smask in Piteå 2011, a very big musical event involving a large number of students from the Luleå University of Technology campus in Piteå, experienced the project management and process. The object of the study has been to find out how models for experience production can be implemented in project management of experience production.The study has been conducted with an inductive and hermeneutic approach. We have made an empirical study of Smask in Piteå 2011, where Sara was project manager, and also studied litterature on the subject experience production and project management. To gather empirics we have used a focus group interview, studies of the project participants evaluations and compilation of Saras own experiences from being project manager.In order to use models for experience production in project management the project manager need to understand the project participant experience and its key elements. These elements are:• Pre- and post experience • The projects entirety • Script/project planning • The mental experiencescapeThese elements affects the participants experience of the project. Project managers can use models for experience production to create better conditions for the project participant experience based on these elements. Validerat; 20110704 (anonymous)